Volver : retorno de los capuchinos españoles al norte de Colombia a finales del siglo XIX (2015)
This article describes the complex sequence of interactions and events that led to the settlement of a mission headed by Spanish Capuchins in Colombia in the late of nineteenth century. It analyses the intellectual conditions that enabled the legitimation, in a Republican context, of the return of the very missionaries who were expelled at the time of the Independence. The author analyses the different registers of justification used by multiple actors involved in this process. He discuses, on the other hand, the material, legal and institutional conditions that made it possible for the Capuchins to consolidate their position within the complex ecclesiastical structure and to establish themselves as indispensable intermediaries for the Colombian State.